Pengaruh Beban Kerja, Disiplin Kerja Dan Kualitas Kerja Terhadap Kinerja Karyawan Pada Klinik Rumah Luka Sidoarjo Di Kabupaten Sidoarjo - Bambang Setyawan; Afi Rachmat Slamet; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determined "The Influence of Workload, Work Discipline and Quality of Work on Employee Performance at the Injury Hospital Sidoarjo Clinic, Sidoarjo Regency". This type of research was a survey research that began in August 2021 with a population of all employees at the Sidoarjo Luka Home Clinic, both medical and non-medical employees. The sampling technique was in the form of total sampling, namely by taking the entire population for research, totaling 33 employees consisting of 20 medical employees (nurses) and 13 non-medical employees. The data analysis technique in this study wass a multiple linear regression analysis technique using SPSS (Statistical Product and Services Solution) software and classical assumption testing. The research data was sourced from primary data and the data collection process used interviews and questionnaires. There are 3 types of questionnaires used, namely: (1) workload instruments with indicators of physical tasks, mental tasks and work organization; (2) work discipline instruments with indicators of obeying time rules, obeying company regulations and obeying behavioral regulations; (3) work quality instruments with reliability indicators in carrying out tasks, giving procedures, and responsibilities. Based on the results of the study, it can be concluded that: Based on the results of the study, it can be obtained that the variables of Workload (X1), Work Discipline (X2) and Work Quality (X3) affect the Employee Performance variable (Y) at the Sidoarjo Injury Home Clinic, with a significant value of each with value of 0.041 < 0.05, 0.013 < 0.05, and 0.026 < 0.0505 with a regression model of Y= 2.776 - 0.414X1 + 0.330X2 + 0.203X3. Simultaneously it can also be said to have an effect on employee performance with a significance value of 0.001 < 0.05. The calculation of the determinant coefficient also produces a value of 0.751 or 75.1%, which means that this research model is declared good because the value of the determinant coefficient is close to 100%. Keywords: Workload, Work Discipline, Quality of Work, Performance, Luka Home Clinic